Trends in Recent World Bank Support for Severance Pay - Mukherjee, Ranjana (World Bank, Washington, DC, 2012)
This note summarizes the operational perspective and design of severance packages supported by Bank loans and credits. The analysis focuses on severance-funding investment projects approved between fiscal 2000 and 2004, during which time revised expenditure eligibility guidelines were issued (in April 2004; see World Bank 2004). Adjustment projects that supported severance were not analyzed because project documents do not separate severance costs from others. The analysis also did not include investment projects that paid consultants to design organizational restructuring or severance packages but that did not fund actual payments to retrenched workers.